Transient Epstein-Barr virus reactivation in CD3 monoclonal antibody-treated patients. - Keymeulen, B; Candon, S; Fafi-Kremer, S; Ziegler, A; Leruez-Ville, M; Mathieu, C; Vandemeulebroucke, E; Walter, M; Crenier, L; Thervet, E; Legendre, C; Pierard, D; et al. (2010)
Here we report a unique situation in which an early and synchronized Epstein-Barr virus (EBV) reactivation was induced by a 6-day course of treatment with a humanized CD3-specific monoclonal antibody in patients with recent onset of type 1 diabetes. The virologic and immunologic analysis demonstrated that this reactivation was transient, self-limited, and isolated, associated with the rapid advent of an EBV-specific T-cell response. The anti-CD3 antibody administration induced short-lasting immunosuppression and minor yet clear-cut signs of T-cell activation that preceded viral reactivation. Early posttransplant monitoring of renal and islet allograft recipients showed that no comparable phenomenon was observed after the administration of full-dose immunosuppressive therapy. This EBV reactivation remains of no apparent clinical concern over the long term and should not preclude further development of therapeutic anti-CD3 antibodies. This phenomenon may also direct new research avenues to understand the still ill-defined nature of stimuli triggering EBV reactivation in vivo.